Strategi Pemasaran Digital untuk Merek Smartphone Mewah: Tinjauan Literatur Sistematis - Khasan Safik; Hani Hasanah; Laras Annisa Ulfitri Nedi (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The development of digital technology has driven major changes in global marketing strategies, particularly in the luxury smartphone industry, where competition is not only based on technological features but also on brand image and exclusivity. This study aims to systematically analyse various digital marketing strategies implemented by luxury smartphone brands using a Systematic Literature Review (SLR) approach. In this study, researchers identified, evaluated, and synthesised 70 related articles, which were filtered into 15 main articles based on inclusion and exclusion criteria between 2020 and 2025. The analysis results indicate that digital marketing strategies such as influencer marketing, search engine optimisation (SEO), visual content on social media, and the use of augmented reality (AR) and virtual reality (VR) technology have proven effective in increasing brand awareness, customer loyalty, and sales conversions. However, the research also reveals the main challenges faced by companies in maintaining exclusivity and premium experiences through digital channels that are mass-market and open in nature. The study recommends that luxury smartphone brands integrate data-driven personalisation approaches and build strong, authentic brand narratives across various digital platforms to maintain their competitive position in the premium segment. The practical implications of this research can serve as a reference for marketers and decision-makers.